Quest over Courses of Study: Deciding for Teacher Rating Scale - Lahiri, Sudeshna (INDIAN EDUCATIONAL REVIEW, 2011)
The focus is now shifting from improvement in the quantity of schools to improvement in the quality of teachers. Hence, reaffirming the role and performance of facilitators become significant in the pursuit of quality education. In this regard, policy makers and administrators have suggested that student evaluation of teachers (SET) should be integral part of the Teacher appraisal. Reviewing the recommendations by different committees for improvement in educational system in India, the question arises — whether questionnaires for rating teachers used to evaluate the teachers should be course specific? What is the status of teachers when they are rated on a uniform questionnaire used in spite of having different streams? Thus, the present study is conducted with a framed objective — to find out the effect of course on student evaluation of teachers. A sample of 1711 higher secondary school students is made to rate 93 teachers. It is found that course has an effect on student evaluation of teachers on more than one dimension of “teacher effectiveness”.